AWARENESS ABOUT DOG BITE MANAGEMENT IN RURAL POPULATION - Kakrani, Vandana Arjun; Jethani, Sumit; Bhawalkar, Jitendra; Dhone, Anjali; Ratwani, Karuna (Indian Journal of Community Health, 2013)
Background-Rabies is a major zoonotic disease that is always fatal common in children less than 15 years of age .Most of the deaths occur due to ignorance about urgency of wound management and vaccine administration after dog bite.Methods-.A cross sectional study was carried out at Rural Health Training Center attached to Dr DY Patil Medical College, Alandi by interviewing the persons accompanying the patients attending the daily outpatient department and those accompanied by no one or children were excluded, similarly in case of more than one person accompanying the patient, only one adult willing to participate was included in the study . Consecutive patients (persons accompanying) attending RHTC OPD were included for the period of one month i.e. May 1st to 31st May 2013. The subjects were asked about whether they had a menace of the stray dogs in their area and questions included were to assess various parameters regarding their awareness about dogbite wound management , vaccine administration and misconceptions associated with it .Results –Out of the 300 respondents majority were in the age group of 26-35 years(39.70% males and 45.10% females). Only 112(37.30%) were aware that the dog should be watched for 10 days after dogbite, even in the areas where stray dog menace was present. A crucial knowledge about severity of bite revealed that 238(79.30%) knew that deep wound at any site is considered as severe bite .Less than 10% knew that bites on head ,face or fingers was also a severe bite. It was encouraging to know that more than 85% i.e. 34(87.2%) out of 39(100%) had of had knowledge that wound should be cleaned with soap and water in areas where stray dog menace was present.Conclusions- The large knowledge gap about various parameters of dog bite management in rural population need to be addressed by well planned extensive health education programme (information about need for urgency of wound treatment, type of first aid, severity of bite, different misconceptions, vaccine awareness etc) with the help of volunteers at local level and Rabies control programme at the national level.